A Technology Acceptance Model (TAM) : Malaysian ESL lecturers’ attitude in adapting flipped learning - Siti Fatimah Abd. Rahman,; Melor Md Yunus,; Harwati Hashim, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Technology Acceptance Model 3 (TAM3) is an inclusive and complex model where it emphasizes the processes that relate to perceived usefulness and perceived ease of use. The model suggests that predictors for perceived usefulness will not influence the perceived ease of use and vice versa. This quantitative research investigates the relationship between computer self-efficacy and computer anxiety (two elements in TAM3) and Malaysian English as a Second Language (ESL) lecturers’ attitude in integrating flipped learning approach. A set of questionnaires was responded by 206 Malaysian ESL university lecturers and the data was analysed using structural equation modelling (SEM). Even though there are a few other studies that show a significant relationship between computer self-efficacy and computer anxiety and ESL lecturers’ attitude in integrating flipped learning, this study found the relationship to be insignificant. According to responses, Malaysian ESL lecturers have no problems in managing basic computer skills. The findings could contribute to future studies that aim to understand user acceptance behaviour. This study could also help decision makers or Malaysian universities in employing or improving the existing flipped learning by identifying the dominant predictors in user acceptance.